68Ga-DOTANOC Focal Pulmonary Activity With No Corresponding CT Abnormality. (December 2016) - Panagiotidis, Emmanouil; Seshadri, Nagabhushan; Fernando, Rashika; Healey, Priya; Vinjamuri, Sobhan
Abstract : Abstract: A 28-year-old woman with medullary thyroid cancer treated with total thyroidectomy and bilateral central and right lateral neck nodal resection postoperatively had increasing calcitonin and carcinoembryonic antigen values. A 68 Ga-DOTANOC PET/CT study performed showed tracer-avid disease in the neck, mediastinal, and hilar lymph nodes. However, there were 3 tracer-avid foci in the lungs bilaterally, suggestive of lung metastases but with no corresponding abnormalities on low-dose CT. A negative contrast-enhanced CT of the lungs along with clinical and radiological follow-up confirmed that the lung activity was artifactual, demonstrating the possibility of 68 Ga-DOTANOC–avid iatrogenic pulmonary microembolism.